Peningkatan Pengetahuan Penanganan Kadar Gula Darah Tinggi pada Penyandang Diabetes Melitus di Prolanis - Okti Sri Purwanti; Astrid Indah Istiningrum; Syarif Fathurozaq Wibowo (Jurnal Abdimas Mahakam, 2022)
People who suffers Diabetes Melitus has high blood sugar levels which is commonly referred to as hyperglycemia. Symptoms that usually appear include frequent urination, thirst, hunger, fatigue, blurred vision, difficulty concentrating, weight loss, and wounds that are difficult to heal. However, a common sign and symptom that patients commonly experience is an increase in blood sugar levels. The purpose of this health education is to increase the knowledge of diabetes melitus patients in handling high blood sugar levels at Prolanis Public Health Center Ngrampal, Sragen Regency, Central Java Province. This health education is carried out directly at the Ngrampal Public Health Center, Sragen Regency. This health education was held on February 19, 2022 at 08.00 WIB to 10.00 WIB, which was attended by 25 participants from diabetes melitus patients. The result of this health education is an increase in the knowledge of diabetic patients regarding the management of high blood sugar levels. During the health education the participants were very enthusiastic so that there were several questions asked by the health education participants. Suggestions from this seminar are that Diabetes Melitus patients are expected to be able to manage and handle independently or with the help of health workers to increase high blood sugar levels (hyperglycemia